Development of young pupils' physical qualities on the systematic approach basis in the physical education process - Shvets Oksana; Kovalchuk Andrii; Bohuslavska Viktoriia; Hlukhov Ivan; Pityn Maryan; Khimenes Khrystyna (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2020)
With help of efforts domestic and foreign authors' there have collected significant data today. They characterize the features of human development in different periods of life. But these data do not allow create a general picture of the physical abilitiessdevelopment in ontogenesis. Purpose of research is to improve the physical education process of 7-9 years-old pupils on the basis of systematic physical education means and methods use and optimization of motor activity. Results. There are established new data of factor decision physical preparedness structure of 7-9 years-old pupils. Test suite analysis, which performed by this age and sex pupils' group, allows selecting, as a rule, a constant number of factors -6. At the age of 7 years these factors make up 81,4-89,6% of the total boys' dispersion sample and 80.2-88.7% of the total girls' dispersion sample; in the 8-year-old -68.0-88.3% at boys and 75.0-87.4% at girls; in the 9-year-old -77.6-88.1% at boys and 83.0-88.3% at girls. The experimental method based on the effective forms, methods and means of junior pupils' physical preparedness increasing. It has been positively influenced at the motor activity volume and physical preparedness indicators. The volume of total motor activity of children has increased to a large extent. There were also positive changes in the control group, but their value was significantly lower. In the experimental group were detected more significant positive changes than in the control group due to higher rates of physical preparedness indicators growth.